2013
DOI: 10.1093/cid/cit599
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postpartum Influenza Vaccination of Mothers and Household Contacts in Preventing Febrile Episodes, Influenza-like Illness, Healthcare Seeking, and Administration of Antibiotics in Young Infants During the 2012-2013 Influenza Season

Abstract: Maternal postpartum vaccination against influenza was associated with a significant reduction of influenza-related morbidity, healthcare seeking, and antibiotic prescription in infants during the influenza season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Several potential mechanisms of protection have been proposed, such as maternal immunization against influenza providing indirect protection of the infant by preventing transmission of influenza virus from the mother to the baby, maternal antibody-mediated protection through transplacental transfer, or maternal antibodymediated protection through breast milk. 10,17,18 Our study suggests that the most likely mechanism of protection of the infants is through the transplacental transfer of maternal antibodies. 10,19,20 The concentration of maternally acquired antibodies decreased rapidly in the infants, and by 16 weeks of age, less than 40% of the infants born to IIV3 recipients had HAI titers of 1:40 or more for any of the vaccine strains, mimicking the reduction in vaccine efficacy.…”
Section: Discussionmentioning
confidence: 75%
“…Several potential mechanisms of protection have been proposed, such as maternal immunization against influenza providing indirect protection of the infant by preventing transmission of influenza virus from the mother to the baby, maternal antibody-mediated protection through transplacental transfer, or maternal antibodymediated protection through breast milk. 10,17,18 Our study suggests that the most likely mechanism of protection of the infants is through the transplacental transfer of maternal antibodies. 10,19,20 The concentration of maternally acquired antibodies decreased rapidly in the infants, and by 16 weeks of age, less than 40% of the infants born to IIV3 recipients had HAI titers of 1:40 or more for any of the vaccine strains, mimicking the reduction in vaccine efficacy.…”
Section: Discussionmentioning
confidence: 75%
“…Illnesses due to influenza also contribute substantially to excess antibiotic use (among both children and household contacts) as well as school and parental work absenteeism [85,129]. One retrospective study found that postpartum immunization and ‘cocooning’ (immunization of household contacts of newborn infants) was associated with fewer childhood febrile illnesses and antibiotic exposures during influenza season [130]. There have been no similar analyses in households of women who were vaccinated during pregnancy, even though routine maternal immunization is likely to be easier to implement than a cocooning strategy.…”
Section: Benefits Of Maternal Influenza Immunizationmentioning
confidence: 99%
“…For older children and adults, the only available vaccine in the market is that against seasonal influenza, although this vaccine has not been included in the expanded program of immunization for children. Immunization of pregnant women relying on the protectiveness of mother-to-child transferred antibodies, and immunization of post-partum mothers and household contacts have been studied as a strategy to reduce influenza virus burden in young children with promising results [130][131][132]. A polyvalent vaccine against RSV and PIV-3 (MEDI-534) is being evaluated in Phase I trials with good safety profile [133].…”
Section: Treatment and Preventionmentioning
confidence: 99%